Assessment of innovations in tutorial method of teaching among medical students - A., Velavan; V, Saravanan; Bazroy, Joy; Singh, Zile (International Journal of Research in Medical Sciences, 2017)
Background: The main focus of a tutorial is to make learning more interactive. Enthusiasm and innovations of tutors make tutorials more effective. This study was done to assess the usefulness of few innovative approaches applied during a tutorial session among medical students. Methods: A total of 84 medical undergraduate students were divided in to seven groups with 12 students in each group with a faculty as a facilitator. A pretest was conducted among the students to assess their knowledge and understanding on the topic of discussion. Then the students were given a review article on the topic of discussion to read followed by group discussion. After this each group was assessed by the way of a quiz programme and individually by a post test. Results: The mean scores obtained in the pretest increased significantly in the post test from 53.6% to 83.7%. Most of the students agreed upon the various advantages of this method of teaching. About 97% of the students rated this method of teaching as good and above. Conclusions: Tutorials are effective methods of teaching medical graduates. The innovations used in this study were well appreciated by the students.